German Society for Immunology and Australasian Society for Immunology joint Workshop 3rd–4th December 2015 – Meeting report. Issue 2 (3rd February 2016) - Kurts, Christian; Gottschalk, Catherine; Bedoui, Sammy; Heinzel, Susanne; Godfrey, Dale; Enders, Anselm
Abstract : The German Society for Immunology (DGfI) and the Australasian Society for Immunology (ASI) hosted the first DGfI‐ASI joint workshop from December 3–4, 2015 in Canberra, Australia. A delegation of 15 distinguished German immunologists discussed the workshop topic "immune regulation in infections and immune mediated diseases" with the aim to establish new German‐Australasian collaborations, discuss new concepts in the field of immune regulation and build a scientific network to create more utilizable resources for excellent (trans‐border) immunological research. The workshop was associated with the 45 th Annual Scientific Meeting of the ASI held from Nov 29–Dec 3, 2015, opening up even more opportunities for finding new collaboration partners. A return meeting will be linked to the annual DGfI meeting that will take place in 2017 in Erlangen.